Comparison between 1.5T and 3.0T MRI: both field strengths sensitively detect subclinical inflammation of hand and forefoot in patients with arthralgia - Krijbolder, Doortje I. (Scand J Rheumatol, 2022)
OBJECTIVES: Magnetic resonance imaging (MRI) of small-joints sensitively detects inflammation. This inflammation, and tenosynovitis in particular, has been shown to predict RA-development in arthralgia-patients. These data have predominantly been acquired on 1.0T-1.5T MRI. However, nowadays 3.0T is commonly used in practice. Evidence on the comparability of these field strengths is scarce and never included subtle inflammation in arthralgia-patients or tenosynovitis. Therefore, we assessed the comparability of 1.5T and 3.0T in detecting subclinical inflammation in arthralgiapatients. METHODS: 2968 locations (joints/bones/tendon-sheaths) in hands and forefeet of 28 patients with small-joint arthralgia, at-risk for RA, were imaged on both 1.5T and 3.0T MRI. Two, blinded readers independently scored erosions, osteitis, synovitis and tenosynovitis (in line with RAMRIS). Features were summed into inflammation (osteitis, synovitis, tenosynovitis) and RAMRIS (inflammation and erosions). Agreement was assessed with intraclass correlation coefficients (ICCs) for continuous scores and after dichotomization into presence or absence of inflammation, on patient- and location-level. RESULTS: Interreader-ICCs were excellent (>0.90). Comparing 1.5 and 3.0T revealed an ICC of 0.90 for inflammation and RAMRIS. ICCs for individual inflammation features were: tenosynovitis 0.87 (95%CI 0.74-0.94), synovitis 0.65 (0.24-0.84) and osteitis 0.96 (0.91-0.98). Agreement was 83% for inflammation and 89% for RAMRIS. Analyses on location-level showed similar results. CONCLUSION: Agreement of subclinical inflammation on 1.5T and 3.0T was excellent. Although synovitis-scores were slightly different, synovitis often occurs simultaneously with other inflammatory signs, suggesting that scientific results on the predictive value MRI-detected inflammation for RA, obtained on 1.5T-MRI, can be generalized to 3.0T-MRI.